Peningkatan Keterampilan SDM dalam Rangka Menunjang Program Destinasi Wisata Mina Politan - Siti Prihatiningtyas; Lukmanul Hakim; Uswatun Niswah; Ahmad Fatoni (UIN Siber Syekh Nurjati Cirebon, 2022)
The Covid-19 pandemic has increased problems related to the capacity of the Human Resources (HR) of the community around Sumurrejo Village, Semarang. Seeing the low quality of human resources